PEMANFAATAN SERBUK KAYU KARET (Hevea brasiliensis) DAN SEKAM PADI SEBAGAI PAPAN PARTIKEL: Utilization of Sawdust Rubber Wood (Hevea brasiliensis) and Rice Husk as a Particle Board - Albayudi Albayudi; Riana Anggraini; Kurniati Pasaribu (Jurnal Silva Tropika, 2021)
ABSTRACT Particle board research continues to be carried out to obtain the right formulation (effective and efficient), both in terms of raw materials and adhesive formulas. The purpose of this study was to determine the nature of particle board from the use of rubber wood powder and rice husk as raw material for particle board with varying levels of phenol formaldehyde adhesive in the manufacture of particle board. This study uses factorial analysis where the first factor is the variation of raw material composition of rubber wood powder and rice husk (75:25%; 50:50%; 25:75%), while the second factor is the variation of phenol formaldehyde adhesive content (6%; 8 %; 10%). This analysis was carried out in a completely randomized design (CRD) with three repetitions. The resulting particleboard was then tested for its physical and mechanical properties according to the JIS A 5908-2003 standard. The results showed that variations in the composition of the raw materials of rubber sawdust and rice husk had a significant effect on moisture content, Modulus of Elasticity, Modulus of Rupture, Internal Bond and screw holding strength. Variations in the adhesive content of phenol formaldehyde have a significant effect on density, moisture content, thickness expansion, water absorption, Modulus of Elasticity, Modulus of Rupture, Internal Bond and screw holding strength. The interaction of variations in the composition of rubber wood sawdust and rice husks has a significant effect on the Modulus of Elasticity, Modulus of Rupture and screw holding strength. Overall, particleboard with the best properties is particleboard with a composition of 75:25% rubber: husk and 10% Phenol Formaldehyde adhesive content, but for the production of 8% phenol formaldehyde adhesive, it is quite good. Keywords: Particle board; Phenol formaldehyde; Rice husk; Rubber wood ABSTRAK Penelitian papan partikel terus dilakukan untuk mendapatkan formulasi yang tepat (efektif dan efisien), baik dari segi bahan baku maupun formula perekat. Tujuan dari penelitian ini adalah untuk mengetahui sifat papan partikel dari pemanfaatan serbuk kayu karet dan sekam padi sebagai bahan baku papan partikel dengan variasi kadar perekat phenol formaldehida dalam pembuatan papan partikel. Penelitian ini menggunakan analisis faktorial dimana faktor pertama berupa variasi komposisi bahan baku serbuk kayu karet dan sekam padi (75:25%; 50:50%; 25:75%), sedangkan faktor kedua adalah variasi kadar perekat phenol formaldehida (6%; 8%; 10%). Analisis ini dilakukan dalam rancangan acak lengkap (RAL) dengan tiga kali pengulangan. Papan partikel yang dihasilkan kemudian diuji sifat fisis maupun mekanisnya menurut standar JIS A 5908-2003. Hasil penelitian menunjukkan bahwa variasi komposisi bahan baku serbuk kayu karet dan sekam padi memberikan pengaruh nyata terhadap kadar air, Modulus of Elasticity, Modulus of Rupture, Internal Bond dan kuat pegang sekrup. Variasi kadar perekat phenol formaldehida memberikan pengaruh nyata terhadap kerapatan, kadar air, pengembangan tebal, daya serap air, Modulus of Elasticity, Modulus of Rupture, Internal Bond dan kuat pegang sekrup. Interaksi dari variasi komposisi bahan baku serbuk kayu karet dan sekam padi memberikan pengaruh nyata terhadap Modulus of Elasticity, Modulus of Rupture dan kuat pegang sekrup. Secara keseluruhan papan partikel yang memiliki sifat terbaik adalah papan partikel dengan komposisi bahan baku karet:sekam 75:25% dengan kadar perekat phenol formaldehida sebesar 10%, namun untuk produksi kadar perekat phenol formaldehida 8% sudah cukup baik. Kata Kunci: Kayu karet; Papan partikel; Phenol formaldehida; Sekam padi